On the development of the zone of weakened bonds that precedes the initiation of Cottrell's crack - Kaminsky, A.A.; Kipnis, L.A.; Polischuk, T.V. (Reports of the National Academy of Sciences of Ukraine, 2018)
The length of the small-scale narrow zone of weakened bonds (prefracture zone) at the point of intersection of the lines of microplastic deformation (slip lines) in the elastic body is found. The prefracture zone is modeled by the line of rupture of a normal displacement. The development of this zone precedes the crack initiation by Cottrell's mechanism. The exact solution of the corresponding problem of the linear theory of elasticity is constructed by the Wiener—Hopf method.